Atlas of implantable therapies for pain management - Deer, Timothy (Springer, 2010)
As of Implantable Therapies for Pain Management This atlas is an essential guide for all implanters, from beginners to the most advanced practitioners. The process of implanting and managing spinal cord stimulators, peripheral nerve stimulators, and intrathecal pumps, from the beginning through long-term management, is thoroughly discussed, as are the prevention and management of complications. Extensive photographs and detailed instructions make each segment a great learning event. The Atlas of Implantable Therapies for Pain Management is a ?must-have? resource for any physician wishing to improve his or her skills in interventional pain treatment. ABOUT THE AUTHOR TIMOTHY DEER, MD, is President and Chief Executive Officer of the Center for Pain Relief in Charleston, West Virginia and Clinical Professor of Anesthesiology, West Virginia University School of Medicine, Morgantown. Dr. Deer is the immediate past Chair of the Committee on Pain Medicine for the American Society of Anesthesiologists; a member of the Boards of Directors of the American Academy of Pain Medicine and the American Society of Interventional Pain Physicians; and a member of the Board of Directors and The Executive Board of the International Neuromodulation Society. He is also Chairman of the Scientific Review Committee of the American Academy of Pain Medicine, Chairman of the Scientific Oversight Committee for Pain Medicine of the American Society of Anesthesiologists, and the current President of The West Virginia Society of Interventional Pain Physicians. He lectures widely on the topic of implantable therapies in pain management and is one of the most respected proponents of these therapies worldwide.